Pre-Order Food System for UNITARIANS - Al-Umyrah, Al-Umyrah; Ashvinie, Natalie Elixha; Kejendran, Yuvatarishinie (IT for Society, 2024)
This Pre-Order Food System for UNITARIANS was created to address common problems experienced by UNITAR student and staff, mainly during peak hours like before break time around 12:30noon to 2:30pm, where long queues and waiting times can disturb their schedules. This platform presents a user-friendly by letting users to login, browse a menu on the menu page, place pre-orders for food and drinks which in this process user need to enter their information, select a suitable pickup time, and make payments either online or cash. A few of user information will be saved inside the database and will be stored safely.